Evaluasi Peforma Jaringan Internet Menggunakan Metode QoS - Aditya Dyan Ramadhan; Iwan Iskandar; Novriyanto; Pizaini (STMIK Budi Darma, 2023)
The use of the internet for learning activities for students aged 5-24 years is increasing rapidly from 33.98% in 2016 to 59.33% of students using the internet in 2020. Pekanbaru Labor Vocational School also uses internet network to support teaching and learning activities. The increasing performance in an internet network will increase the data traffic. The problem that arises is the length of time needed to access the internet so as to reduce learning productivity. QoS method is conducted in this research to analyze internet access speed and measure internet network performance in Pekanbaru Labor Vocational School. Based on the measurements taken, it can be seen that the throughput value obtained is an average throughput of 2191 Kbps, the delay value obtained is 5.70 ms, the packet loss value obtained is 1.3%, the jitter value obtained is 0.00854421ms. This value is the value of network speed measured using the QoS method by accessing several sites including www.youtube.com, www.detik.com and also the download speed. It can be concluded that referring to the TIPHON standard, the Quality of Service value obtained by SMK Labor Pekanbaru is classified as very good with an index of 4 and a percentage of 95-100%.